How NFTs could transform health information exchange - Kostick-Quenet, Kristin; Mandl, Kenneth D; Minssen, Timo; Cohen, I Glenn; Gasser, Urs; Kohane, Isaac; McGuire, Amy L (Science (American Association for the Advancement of Science), 2022)
[Figure: see text].